2004
DOI: 10.1191/0267659104pf737oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Duraflo II-coated cardiopulmonary bypass circuit and a trillium-coated oxygenator during open-heart surgery

Abstract: There were small differences in the inflammatory response between the two extracorporeal circulation devices compared in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Eynden et al [12] compared outcomes in patients undergoing CPB with either an Avecor oxygenator with Trilium or an uncoated circuit and found that the Avecor circuit decreased intra-operative blood loss during surgery without affecting overall blood transfusion requirements. Hoel et al [13] compared outcomes in patients undergoing CPB with either the Trillium or Duraflo II (heparin-bonded) circuits. They documented an earlier increase in the β-thromboglobulin concentration in the Trillium group but found no other significant differences in outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Eynden et al [12] compared outcomes in patients undergoing CPB with either an Avecor oxygenator with Trilium or an uncoated circuit and found that the Avecor circuit decreased intra-operative blood loss during surgery without affecting overall blood transfusion requirements. Hoel et al [13] compared outcomes in patients undergoing CPB with either the Trillium or Duraflo II (heparin-bonded) circuits. They documented an earlier increase in the β-thromboglobulin concentration in the Trillium group but found no other significant differences in outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the fact that while age is associated with a low-grade inflammatory state, 5,13,14 upregulation of the inflammatory response and microvascular blood flow tends to decline with age. [15][16][17][18][19] In addition, studies have shown that when comparing postoperative elderly patients who developed NCD versus those who did not, there was no difference in preoperative inflammatory markers between groups. 18,20 Evaluated with our current study, this may mean that although elderly patients do experience NCD, systemic inflammation may be a more direct mechanism in younger versus older patients.…”
Section: Cytokine Analysismentioning
confidence: 99%
“…60 In a recently published randomized controlled trial comparing the Duraflo II totally heparin-coated CPB system with the Trillium Biopassive surface-coatedAffinity oxygenator (Medtronic, Inc., Minneapolis, MN, USA), only small differences in the inflammatory response between the two extracorporeal circulation devices were noticed. 61…”
Section: Strategies To Improve Biocompatibility Of the Extracorporealmentioning
confidence: 99%